2002
DOI: 10.1111/j.1572-0241.2002.05680.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of missed advanced adenomas on surveillance colonoscopy

Abstract: The present study shows an advanced polyp miss rate that is comparable with other studies even in a fellowship training setting. Prospective studies with tandem surveillance colonoscopy are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Several previous studies reported that the miss rates for total polyps, adenomas, and advanced adenomas were 16.8% to 28%, 16% to 26%, and 1.7% to 11%, respectively 910111213141517. The variation in adenoma miss rates between studies may be caused by heterogeneity in study design.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several previous studies reported that the miss rates for total polyps, adenomas, and advanced adenomas were 16.8% to 28%, 16% to 26%, and 1.7% to 11%, respectively 910111213141517. The variation in adenoma miss rates between studies may be caused by heterogeneity in study design.…”
Section: Discussionmentioning
confidence: 97%
“…Cecal intubation, adequate bowel preparation, and a colonoscopic withdrawal time of 6 minutes or more are suggested to ensure complete removal of polyps and improvement of polyp detection based on previous studies 78. Despite these efforts, it has been reported that a significant number of polyps are missed during surveillance colonoscopy,91011121314151617 thereby leading to the development of interval cancers from the missed neoplastic polyps 18. Based on several tandem or consecutive colonoscopy studies,912131415 the miss rate of polyps is reported to be 16.8% to 28%.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1997, when the US agency for Health Care Policy and Research first advocated widespread colon cancer screening, refinements in techniques of optical colonoscopy (OC), barium enema (BE), and flexible sigmoidoscopy (FS) have evolved [2,3]. Each examination has a failure rate, ranging from a low of 4% for colonoscopy in right-sided cancers to 46% for FS [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Failed diagnoses are well known to clinicians, but the relative failure rates for the three most widely used screening examinations in community hospitals are not.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the overestimation and limitation in terms of determining the incidence and characteristics of interval CRC have been resulted. 12 17 In fact, a number of endoscopists have concerned about the incidence of unpredicted CRC soon after their index colonoscopy during the period of surveillance for each patient.…”
Section: Introductionmentioning
confidence: 99%